Teenage pregnency: Do they have adverse outcomes? - Deeyagaha Waduge, R.P.K (My University, 2004)
Objective of the study is to compare the proportions of unplanned pregnancies and the pregnancy outcome in teenagers and other woman. Teenage pregnancies especially those below 17 years of age have a significantly higher link of worker outcomes. A large proportions of those pregnancies in unplanned and could be presented by counseling